(untitled) (Forum Theologicum Sardicense, 2025)
Ivo Yanev, Prof. N. N. Glubokovsky and Theological Education Reform in Russia in the Late 19th and the Early 20th c. (On the Education of the Priests). This article aims to explore some of Professor N. N. Glubokovsky‘s views on the reform of spiritual education in Russia at the end of the nineteenth and the beginning of the twentieth century, particularly concerning the training and education of pastors in the Orthodox Church. It is based on his book In Matters of Religious Schools (Middle and High) and the Educational Committee in the Holy Synod, published in 1907 in St. Petersburg, Russia.